Produção de Enzimas Oxidativas por Fungos Amazônicos Degradadores de Madeira - Fonseca, Maria Dolores Pinheiro (2009)
The degrading Amazonian fungi wood Datronia brunneoleuca, Lentinus crinitus, Trametes lactinea and Xylaria sp were evaluated in five ways of solid culture being them: extract of jerimum, sugarcane bagasse, fish meal, extract of malte and BDA, in pHs 4, 5, 6, 7 and 8 and temperatures 28º and 30ºC. The measures of the micelial growth had been taken in two perpendicular directions for each 24 hours until it completed the diameter Petri dishes. Medium tested industrials (Malte and BDA), cepas Amazonian of Datronia brunneoleuca, Trametes lactinea and Lentinus crinitus presented good answer to the average growth in synthetic way of extract of malte in the temperature of 30ºC however, the other ways had contributed to the growth of the fungi, confirming that each fungu has its specifics nutricionais requirements. The best result for radial growth of the fungi tested in synthetic way was extract of malte and temperature 30º C where it got the great absolute value of growth for Datronia brunneoleuca,Trametes lactnea and Lentinus crinitus. While the best pH for growth of the fungi is in the range of 4-5. For determination of the micelial mass, it was used the growth in liquid medium extract of jerimum and after 5, 10. 15, 20, 25 and 30 days the micelial mass were calculated by the difference in relation to the dry weight (in greenhouse 70ºC). The percentage of micelial mass produced was determined in the end of the experiment and to each five days of incubation. In terms of absolute values the great production occurred for Datronia brunneoleuca and the minor for Xylaria sp. In general, with exception to Xylaria sp, the fungus had presented percentage of production of micelial mass very near with a difference around 63% between them. For determination of the activities of lacase, fenoloxidasel and peroxidase, in temperature 28º C, without light, in stationary condition. The fungi had been cultivated in liquid medium extract of jerimum contend 3% of Tween 80 and 3% of magnesium sulphate. The basidiomycetes produce enzymes ligninolític of constituent form; however they can be induced for the culture conditions. The results of the present research showed that Amazonian fungi used with the addition of Tween-80 contributes to the increase of the secretion of lacase and peroxidase. In general, it did not have statistics difference in fenoloxidase activity and peroxidase between the tested fungi, with exception for Xylaria sp that showed difference only in relation the Lentinus crinitus. It can be concluded that the liquid medium of jerimum added of surfactante, dextrose and sulphate of magnesium is adjusted for attainment of great micelial density for the fungi Datronia brunneoleuca, Trametes lactinea and Lentinus crinitus and the use of Tween- 80 in the liquid medium contributes for the increase of the secretion of lacase for the tested fungus.There is a positive relation between the enzymatic activity and production of micelial mass in the fungi studied here.